2005
DOI: 10.1042/bj20050845
|View full text |Cite
|
Sign up to set email alerts
|

Lectin-like oxidized low-density lipoprotein receptor-1 (LOX-1) transcriptional regulation by Oct-1 in human endothelial cells: implications for atherosclerosis

Abstract: LOX-1, a receptor for ox-LDL (oxidized low-density lipoprotein), has recently been determined to play a critical role in the progression of atherosclerosis. LOX-1 expression (mRNA and protein) has been shown to be up-regulated by pro-atherogenic stimuli, such as ox-LDL and Ang II (angiotensin II). However, the molecular mechanisms of these up-regulations are unclear. In the present study, we explored LOX-1 transcriptional promoter activation in response to ox-LDL and Ang II. Under basal states, LOX-1 core prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 35 publications
5
36
0
Order By: Relevance
“…In this study, we did not observe the complete blockade of NF-B activity by the siRNA; we postulate that it is caused by the relatively low transfection efficiency of endothelial cells, as we observed previously. 13 This explanation is supported by the observation that NF-B p65 subunit is still expressed in p65 NF-B siRNA plasmid-transfected cells, though the expression is marked lower than that in cells without transfection. Accordingly, because not all cells are transfected with siRNA plasmid, it is not surprising that p65 NF-B siRNA cannot completely block Ang II-mediated NF-B activation or LOX-1 promoter activation in HCAECs.…”
Section: The Critical Role Of Nf-b In Ang Ii-induced Lox-1 Promoter Asupporting
confidence: 72%
See 3 more Smart Citations
“…In this study, we did not observe the complete blockade of NF-B activity by the siRNA; we postulate that it is caused by the relatively low transfection efficiency of endothelial cells, as we observed previously. 13 This explanation is supported by the observation that NF-B p65 subunit is still expressed in p65 NF-B siRNA plasmid-transfected cells, though the expression is marked lower than that in cells without transfection. Accordingly, because not all cells are transfected with siRNA plasmid, it is not surprising that p65 NF-B siRNA cannot completely block Ang II-mediated NF-B activation or LOX-1 promoter activation in HCAECs.…”
Section: The Critical Role Of Nf-b In Ang Ii-induced Lox-1 Promoter Asupporting
confidence: 72%
“…In a recent study, we found that a distinct promoter region, between nt Ϫ1595 and Ϫ1494, is required for LOX-1 promoter activation in response to oxLDL. 13 There could be 2 explanations for this observation. First, Ang II and oxLDL both induce intracellular oxidative stress, which then activates the same transcription factor.…”
Section: Analysis Of Ang Ii-induced Lox-1 Promoter Activationmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been demonstrated that ECs apoptosis induced atherosclerotic lesion development and plaque shedding [3][4][5]. Oxidized Low-Density Lipoprotein (ox-LDL), an important atherosclerotic risk factor, may induce ECs apoptosis during the pathogenesis of AS [6][7][8]. Hence, inhibition of ox-LDL induced ECs apoptosis may suggest new therapies in the AS treatment.…”
Section: Introductionmentioning
confidence: 99%